Upaya Meningkatkan Kemampuan Motorik Halus Anak Melalui Media Plastisin 3 Dimensi pada Kelompok B TK Dharma Wanita 1 Mojotengah Kecamatan Kedu Kabupaten Temanggung Semester I Tahun Pelajaran 2017/2018 - Sumirah Sumirah (Universitas PGRI Semarang, 2020)
Fine motor skills are abilities that involve certain parts of the body and use a group of small muscles such as using the fingers and wrist movements which often require precise eye and hand coordination such as writing, drawing, holding things with the thumb and forefinger , and others. The problem that occurs so that this classroom action research is held is the low fine motor skills of the Group B children TK Dharma Wanita 1 Mojotengah. The objectives of this study are: 1) To find out that through 3-dimensional plasticine media can improve the fine motor skills of Group B children TK Dharma Wanita 1 Mojotengah Kedu Temanggung Semester I Academic Year 2017/2018, 2) To determine the magnitude of the increase in fine motor skills of children through 3-dimensional plasticine media in Group B children TK Dharma Wanita 1 Mojotengah Kedu Temanggung Semester I Academic Year 2017/2018. The subjects of this study were 13 students of Group B TK Dharma Wanita 1 Mojotengah. The research was conducted in November 2017. The data collection methods used were observation, documentation and interviews. Based on the results of research and discussion, it can be concluded that through learning activities using 3-dimensional plasticine media, the fine motor skills of Group B children TK Dharma Wanita 1 Mojotengah can be improved. This can be proven by an increase in the child's fine motor skills from before the action or pre-cycle only 15.4%, Cycle I reached 46.1% and Cycle II reached 84.6%. Therefore, efforts to improve the fine motor skills of the children in Group B TK Dharma Wanita 1 Mojotengah can be said to be successful because they have met the predetermined maximum percentage, namely 80%, marked by skill and neatness in making shapes, the ability of children to add other forms to existing forms, composition. or a proportional and attractive shape.